Upaya Guru PAI dalam Membina Akhlak Peserta Didik melalui Pembiasaan Kegiatan Keagamaan di SMA YBKP3 Garut - Annisa Rahmawati Hidayat; Nan Rahminawati; A. Mujahid Rasyid (Bandung Conference Series: Islamic Education, 2022)
Abstract. The teacher's efforts affect the success of students in learning, both in a change in attitude and in increasing the ability of the students themselves. The purpose of this study is (1) to find out what steps are taken by PAI teachers in fostering the morals of students at SMA YBKP3 Garut (2) to describe the methods used by PAI teachers to foster students' morals at SMA YBKP3 Garut (3) to find out what alone which is a factor supporting and hindering the efforts of PAI teachers in fostering the morals of students at SMA YBKP3 Garut. This research is an empirical research using a qualitative descriptive approach. Data collection techniques in this study used the methods of observation, interviews, and documentation. This qualitative research uses theoretical and empirical activities and is presented in the form of a narrative text to explain clearly how the steps of learning, learning methods, as well as supporting and inhibiting factors experienced by PAI teachers in fostering the morals of students through habituation of religious activities. Abstrak. Upaya guru mempengaruhi keberhasilan siswa dalam belajar, baik dalam perubahan sikap maupun dalam meningkatkan kemampuan siswa itu sendiri. Tujuan penelitian ini adalah (1) untuk mengetahui langkah-langkah apa saja yang dilakukan guru PAI dalam membina akhlak siswa di SMA YBKP3 Garut (2) mendeskripsikan metode yang digunakan guru PAI untuk membina akhlak siswa di SMA YBKP3 Garut ( 3) untuk mengetahui apa saja faktor pendukung dan penghambat upaya guru PAI dalam membina akhlak siswa di SMA YBKP3 Garut. Penelitian ini merupakan penelitian empiris dengan menggunakan pendekatan deskriptif kualitatif. Teknik pengumpulan data dalam penelitian ini menggunakan metode observasi, wawancara, dan dokumentasi. Penelitian kualitatif ini menggunakan kegiatan teoritis dan empiris dan disajikan dalam bentuk narrative text untuk menjelaskan secara gamblang bagaimana langkah-langkah pembelajaran, metode pembelajaran, serta faktor pendukung dan penghambat yang dialami guru PAI dalam pembinaan akhlak siswa melalui pembiasaan kegiatan keagamaan.